SYNTHESIS AND STRUCTURAL CHARACTERIZATION OF COPPER (0) NANOPOWDER OBTAINED USING MICROWAVE TECHNIQUES(MW) AND SOLVOTHERMAL HIDRATION REACTION at high pressure (HP) use SUPERCRITICAL FLUIDS (FSC) - Guzmán D., A. (2013)
This paper describes the synthesis of copper (0) nanopowder via MW and SCF. From CuSO4.5H2O, CuO was obtained and from this precursor copper Formate (II) was synthesized with MW radiation of a household oven at 30% of power, for a period from 4 to 6 hours. Then, keeping the same power, reflux system is changed by a buld distillation, where the powders of copper (0) are obtained by decomposition of the precursor which autocatalized at (368-436 °K),this reducing conditions allows the transformation from Cu (II) to Cu (0). Also high volumes of Cu(0) nanopowder, were obtained using ethanol as SCF, in a reducing atmosphere of H2, at Tmax 270° C and at Pmax 2425 psi in a microreactor PARR model 4560 (100mL, 200 bars) applied on the copper precursor. The products were characterized by UV, XRD, FTIR, FRX.